Fabrication of Step−Index Fluorotellurite Fibers with High Numerical Aperture for Coherent Mid—Infrared Supercontinuum - Yu Li; Meisong Liao; Jianjun Han; Jie Luo (Crystals, 2022)
We demonstrate the fabrication process and coherent supercontinuum (SC) generation of fluorotellurite step−index fibers with a high numerical aperture (0.56 and 0.64 at 1552 nm). Two compatible fluorotellurite glass pairs were first explored for fiber fabricating with built−in casting and rod−in−tube techniques in a glovebox. Coherent SC sources from 1200 nm to 2400 nm were generated from the fluorotellurite step−index fibers pumped by a femtosecond fiber laser at 1560 nm. Owing to the excellent dehydration of the fluoride, such fibers are available and promising nonlinear media for achieving coherent mid−infrared (MIR) SC.